Performance and Lubrication Mechanism of New TiO2 Nanoparticle-Based High-Performance Lubricant Additives. Issue 2 (22nd February 2021) - Dassenoy, Fabrice; Jenei, Istvan Z.; Pavan, Sophie; Galipaud, Jules; Thersleff, Thomas; Wieber, Stephan; Hagemann, Michael; Ness, Daniel
Abstract: The tribological performance of polymer-stabilized TiO2 particles dispersed in mineral base oil was investigated. Two polymer–TiO2 mass ratios were investigated, with a constant polymer concentration of 0.3 wt% and two nanoparticle concentrations of 0.1 and 1 wt%. Friction tests were carried out with a pin-on–reciprocating flat test configuration under boundary-lubricated sliding conditions in the presence of a steel–steel contact and at two temperatures (20 and 100 °C). The results show the very good antiwear performance of the nanoparticle-based dispersions. The most promising results were obtained with 0.1 wt% TiO2 particles and at 20 °C. At this temperature, the wear resistance properties of the TiO2 particles surpass those of zinc dialkyldithiophosphate (ZDDP). The tribofilms generated during the friction tests were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM) combined with energy-dispersive X-ray spectroscopy (EDS) and electron energy loss spectroscopy (EELS), and X-ray photoelectron spectroscopy (XPS). A tribofilm composed of agglomerates of TiO2 particles embedded in a matrix formed by the polymer was observed. The combination of the polymer used as a dispersant and the TiO2 particles allows good tribological performance that was observed during the friction tests. The formulation including TiO2 particles could improve the antiwear properties of materials in an environment where conventional wear reducing additives do not form tribofilms due to low temperatures.